1986
DOI: 10.1037/0003-066x.41.2.159
|View full text |Cite
|
Sign up to set email alerts
|

The dose–effect relationship in psychotherapy.

Abstract: In order to specify the relationship between length of treatment and patient benefit, probit analysis was applied to 15 diverse sets of data frorn our own research and from research previously reported in the literature. These data were based on over 2,400 patients, covering a period of over 30 years of research. The probit model resulted in a good fit to these data, and the results were consistent across the various studies, allowing for a meta-analytic pooling that provided estimates of the expected benefits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

70
839
17
40

Year Published

1996
1996
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,215 publications
(966 citation statements)
references
References 19 publications
70
839
17
40
Order By: Relevance
“…On the basis of these data, AMI treatments produced client improvement rates for alcohol and/or drug addiction (51%) that were at least equal to rates generated by empirically supported treatments for depression and panic disorder. Moreover, on the basis of over 2,400 clients, Howard et al (1986) reported that 50% of clients improved in eight sessions of psychotherapeutic treatment-yet AMIs yielded these same improvement rates in an average of just two sessions.…”
Section: Benchmarks For Comparisonmentioning
confidence: 99%
“…On the basis of these data, AMI treatments produced client improvement rates for alcohol and/or drug addiction (51%) that were at least equal to rates generated by empirically supported treatments for depression and panic disorder. Moreover, on the basis of over 2,400 clients, Howard et al (1986) reported that 50% of clients improved in eight sessions of psychotherapeutic treatment-yet AMIs yielded these same improvement rates in an average of just two sessions.…”
Section: Benchmarks For Comparisonmentioning
confidence: 99%
“…Psychotherapy researchers are interested in the effects of treatment type and modality to identify the most efficacious treatments, and these may be important variables in establishing any benchmark. Number of weeks in treatment was included, as the dose-effect relationship in psychotherapy is well documented (e.g., Howard, Kopta, Krause, & Orlinsky, 1986). Finally, sample size of the individual studies was included, as studies with smaller sample sizes may have larger effect sizes based on statistical power and publication bias toward studies with statistical significance (Quintana & Minami, 2006).…”
Section: Moderator Analysismentioning
confidence: 99%
“…They suggest that the intervention tapped into the variables responsible for behavioral change in a predictable manner (Howard, Kopta, Krause,&Orlinsky, 1986).…”
Section: Dose-response Relationmentioning
confidence: 99%